2002
DOI: 10.1074/jbc.m205657200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Characterization of Substrate and Inhibitor Binding Sites of a Glycosyl Hydrolase Family 11 Xylanase fromAspergillus niger

Abstract: The importance of aromatic and charged residues at the surface of the active site of a family 11 xylanase from Aspergillus niger was evaluated using site-directed mutagenesis. Ten mutant proteins were heterologously produced in Pichia pastoris, and their biochemical properties and kinetic parameters were determined. The specific activity of the Y6A, Y10A, Y89A, Y164A, and W172A mutant enzymes was drastically reduced. The low specific activities of Y6A and Y89A were entirely accounted for by a change in k cat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 51 publications
6
40
0
Order By: Relevance
“…These hypotheses based on the combinatorial exploration of the thumb region and accompanying sequence analyses were confirmed experimentally by testing the inhibitor sensitivity of a limited set of recombinantly expressed XynII mutants. The finding that Asn at position 124 of XynII is critical for XIP-I-sensitivity of this GH11 endoxylanase agrees with data obtained for another GH11 endoxylanase, ExlA from A. niger, as mutation of the corresponding Asn to Ala (ExlA-N117A) led to abolition of ExlA-XIP-I complex formation (Tahir et al, 2002). Furthermore, our results are consistent with the recently reported crystal structures of XIP-I and TAXI-I in complex with GH11 endoxylanase XynC of P. funiculosum and ExlA (Sansen et al, 2004), respectively.…”
Section: Interpretation Of Screening Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…These hypotheses based on the combinatorial exploration of the thumb region and accompanying sequence analyses were confirmed experimentally by testing the inhibitor sensitivity of a limited set of recombinantly expressed XynII mutants. The finding that Asn at position 124 of XynII is critical for XIP-I-sensitivity of this GH11 endoxylanase agrees with data obtained for another GH11 endoxylanase, ExlA from A. niger, as mutation of the corresponding Asn to Ala (ExlA-N117A) led to abolition of ExlA-XIP-I complex formation (Tahir et al, 2002). Furthermore, our results are consistent with the recently reported crystal structures of XIP-I and TAXI-I in complex with GH11 endoxylanase XynC of P. funiculosum and ExlA (Sansen et al, 2004), respectively.…”
Section: Interpretation Of Screening Resultssupporting
confidence: 85%
“…To address this question, we applied the previously developed phage display system to explore the potential for diversification of the inhibition profile of GH11 endoxylanases (Table 2) by screening a combinatorial library. The library was focussed on the 'thumb' region of GH11 endoxylanases, as Aspergillus niger endoxylanase ExlA lost XIP-I sensitivity upon site-directed mutagenesis in its thumb region (Tahir et al, 2002). The crystal structure of endoxylanase-inhibitor complexes confirmed that the thumb region indeed constitutes an important interaction site not only for XIP-type inhibitors but also for TAXI-type inhibitors (Sansen et al, 2004).…”
Section: Discussion Design and Construction Of The Xynii Combinatoriamentioning
confidence: 97%
“…Inhibition of fungal xylanases is not due to the binding of XIP-I to glycodecorations, because both the native and Escherichia coli-derived recombinant forms of P. funiculosum xylanase are inhibited to the same extent. Recent site-directed mutagenesis studies have shown that XIP-I binds to the conserved "thumb" hairpin loop of GH11 xylanases (13); however, the mechanism by which the inhibitor recognizes these structures and how the plant protein interacts with GH10 enzymes is unknown.…”
Section: The Xylanase Inhibitor Protein I (Xip-i) From Wheatmentioning
confidence: 99%
“…Primer sequences are boxed. Tahir et al, 2002). Based on structural analysis, both endoxylanase A and B belong to family 11.…”
Section: Figmentioning
confidence: 99%